Factors influencing youth engagement in agriculture upstream activities - Mohamad Fadzil, Mohamad Afeeq (2018)
Agriculture sector in Malaysia is considered as one of the most important sector due to its contributions to the country. Agriculture sector played an important role and has a lot of potential in contributing into Malaysia’s economy growth. However, the agriculture sector in Malaysia is labour intensive to make sure that agriculture productions can be done smoothly. Policies have been constructed by the government to tackle problems in the agriculture sector, promoting youth involvement and at the same time help improving the agriculture sector in Malaysia. However, despite the efforts and implementation of these policies by the Malaysian Government the involvement of youth in the agriculture sector in Malaysia is still low compared to their involvement in other more popular sectors. This research is conducted to identify factors influencing youth engagement in agriculture upstream activities. The factors are subjective norms, knowledge, attitude, negative perception and perceived behavioural control. The respondents of this research were those between the age of 15 – 40 years old since it is the age range for youth. Based on the results collected and analysed, Subjective norms or external factor proved to be the most contributing factor among other factors. Out of all the factors, attitude is the only factor that does not influence youth intention to participate in agriculture upstream activities.